Effectiveness of Cardamom Ethanol Extract (Amomum compactum Soland Ex Maton) in Inhibiting the Growth of Candida albicans Biofilm - Masfufatun; Zahra, Fatimatuz; Listyawati, Agusniar Furkani (Poltekkes Kemenkes Surabaya, 2025)
Cardamom (Amomum compactum Soland Ex Maton) is a spice known for its pharmacological properties. It contains bioactive compounds such as flavonoids, alkaloids, saponins, terpenoids, and tannins, which have the potential antibiofilms activity. This study aims to evaluate the effectiveness of cardamom ethanol extract in inhibiting the growth of Candida albicans biofilm. A true experimental design with a post-test only control group design approach was employed. The extraction method used is the maceration method, and biofilm inhibition was assessed using the microtiter plate biofilm assay method. The Optical Density (OD) value was measured at 595 nm using a microplate reader . The results indicate that cardamom ethanol extract significantly inhibited C. albicans biofilm growth (p<0.05). The highestinhibition was observed at a 50% concentration of Cardamom extract. Probits analysis revealed the minimum biofilm inhibitory concentration (MBIC50 ) of cardamom extract to be 21.768%. In conclusion, cardamom ethanol extract is effective in inhibiting C. albicans biofilm formation with significant activity observed at concentration as low as 3.175, with the highest efficacy at 50%. Thus, cardamom ethanol extract can be used as an antibiofilm for the treatment of various infectious diseases caused by C. albicans biofilm. The findings suggest that cardamom ethanol extract could serve as a promising candidate for the development of novel antibiofilm agents targeting C. albicans infections. Further research, particularly in vivo studies, is necessary to validate its therapeutic potential and explore its mechanism of action in clinical settings.